Duties and Responsibilities of Principal's Management on Quality of Early Childhood Education - Nipriansyah, Nipriansyah; Intamano, Banthita (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
The purpose of this study was to obtain an overview of the duties and responsibilities of the principal's education management towards quality Early Childhood Education (PAUD). This research uses library research methods, namely research carried out through collecting data or scientific writings that aim at the object of research or data collection that is library in nature, or studies carried out to solve a problem which is basically focused on critical and in-depth study. to relevant library materials. The results of the study show that the management functions are decision making, organizing, staffing, planning, supervising, communicating and directing. And the role of the principal in improving the quality of education is as an educator, manager, administrator, supervisor, leader, innovator, and motivator. The role of the principal in order to improve the quality of education is very important, because it can affect the success or failure of the quality of education.